Experiências formativas: contribuições dos encontros pedagógicos para a formação continuada de educadores - Mutuípe-BA - Brito, Eliete Barreto (2011)
This dissertation presents contributions of pedagogical meetings (Formative Experiences) for the training of educators. It is a qualitative research which had written records as empirical source. The analysis of this material and the elaboration of the text articulate the study in three pedagogical constants. The first constant reflects the question of ritual memory in pedagogical coordination, emphasizing the movement, the coming and going as a constitutive element of praxis; and the contextual environment as a part of the formative process as well as a part of praxis. The second constant presents the reflection as a path to the (re)construction of knowledge, built from two aspects: education and training. The first aspect points to the reflection of scientific concepts mistakenly used; the second aspect highlights the reflection on praxis as the discovery of themselves, where the concepts of learning build different ongoing experiences. The third constant of the Formative Experience shows four methodological pillars that integrate the Circle of Knowledge as elements of accounting of missing knowledge. In this way, being, doing, knowing and livingtogether receive an special emphasis; and the pedagogical coordinator is responsible for spying the need of keeping awake the core values of knowledge, in order to educate and train themselves, collectively; in order to share the enchantment of cooperation, mutuality and joy of learning and living together. This last pedagogical constant, that is, the last chapter, presents two aspects of study: the management of spirituality as an ethical-political perspective of coordination. The first aspect reveals the need of rejecting the pragmatic and the need of accepting the paradigmatic in the coordinator task. The second aspect is a contribution for the construction of a new concept, possible to be taught, in order to build a more humane way of teaching through the political-pedagogical management.